Analalisis Aspek Kombinasi Tingkat Kreaktivitas Desain Produk Mahasiswa Fisika pada Pembelajaran Fisika Dasar - Krismonika, Zuliana; Eddie, Sukiswo Supeni (UPEJ Unnes Physics Education Journal, 2021)
The 21st Century skills that need to be reached at the top of the learning process according to the revised Bloom Taxonomy is creativity. According to Rhode’s creativity can be reviewed through the 4P approach of Person, Press, Process, and Product. Peter Nilsson divides the analysis of product creativity into; imitation, variation, combination, transformation, and original creation. Combination is taking two existing works and then combining them. The research was conducted by giving an assignment to design Contest of Wits Buzzer (LCC) products by applying the creativity of the combination aspects. Then the product design was assessed by all college students who are competent in their fields and researchers uses instruments that have been validated by expert. The assessment results are then analyzed using simple descriptive statistics in the form of means, median, and mode. Based on the results of descriptive statistical analysis, it was found that the combination of creativity products design of students is included in the group of a very high score with an assessment score of 5.7 on a scale range 1-7.